Immunization of mice with plasmid DNA expressing the measles virus nucleoprotein gene - Fooks, A R; Jeevarajah, D; Warnes, A; Wilkinson, G W; Clegg, J C (Viral immunology, 1996)
The measles virus (MV) nucleocapsid (N) protein gene has been inserted into a plasmid vector so as to place the gene under the control of the strong constitutive human cytomegalovirus major immediate early promoter. On intramuscular injection of pMV64 DNA into C3H/He mice, seroconversion with increasing titers of N-specific serum IgG antibodies was observed over a period of 3 months. However, when 3-week-old mice were immunized by intramuscular injection of pMV64 in a two-dose schedule, and challenged intracranially with a rodent-adapted measles virus strain (CAM/RB) at 5 weeks of age, no significant protective response was seen. The lack of effective protection evoked by DNA immunization in this model, where MV challenge must take place before 8 weeks of age, may be due to inefficient induction of cell-mediated immunity resulting from expression in muscle tissue, compounded by a relatively slow rise in immune response compared with that seen with the recombinant adenovirus.